Africa's evolving career civil service systems: three challenges - state continuity, efficient service delivery and accountability - Adamolekun, Ladipo (2002)
This article examines the crisis of the career civil service systems in Sub-Saharan African (SSA) countries in the 1990s against the background of the progressive abandonment of the key features of the Weberian bureaucratic models inherited by the countries at independence in the 1960s. After analysing the major explanatory factors for the crisis (adoption of one-party systems, advent of military governments and the triumph of patronage over the merit system) and the consequent decay of the institutions in many countries, the efforts made to rehabilitate the institutions in the 1990s are assessed. The assessment pays particular attention to the two strong developmental trends of the decade: simultaneous establishment of functioning market-friendly economies and functioning democratic governments. The article concludes by proposing the redesign of Africa's career civil service systems with a view to addressing three key challenges that are critical to achieving and sustaining functioning market economies and functioning democracies: state continuity, efficient service delivery and accountability of the governors to the governed. Specific changes to the career civil service systems that are proposed include, among others, clear separation of political from career appointments: the introduction or increased use of contract appointments at managerial and technical professional levels (as a transititional arrangement); and de-linking local governments and parasytatals from the civil service. The critical importance of an enabling sociopolitical and economic environment for a civil service capable of tackling the three challenges is also emphasized. - Reproduced.
Keywords: Civil service - Africa; Civil service